Os causos em Quirinópolis: práticas e representações culturais (1940-1970) - Silva, Flavia Rosa de Moraes (2010)
This work aims to recognize the social dimension developed by stories in the first decades of the twentieth century that are still part of Quirinópolis culture. This research aimed to discuss the motivation of the constant practice of passing the stories to the younger people in rural areas in the period above mentioned. Thus, it aims identify the dimension developed by stories in the social context through orality and, therefore, identify the control and especially the social cohesion they have on community people between the 40 and 70 decades. There are high differences in old people speaking, and at the same time an overlap between rural and urban areas, which encourages a rethinking of these spaces as different and complementary, besides, they reflect the reframing of the stories told by elders of the local community. Recognizing the importance of these stories requires recognizing the social changes and not the nostalgia in this perspective, because each society in its epoch has the mechanisms of social cohesion, a reinforced fact by Quirinópolis stories